Factors Influencing the Perceived Employability among University Students - Zou, Longxiang; Appalanaidu, Sathish Rao; Nachiappan, Suppiah (South Asian Journal of Social Sciences and Humanities, 2024)
The global economic turmoil and the employability gap among university students have created a challenging job market for graduates. It is crucial to understand the factors that shape students’ perceived employability and to implement effective measures to address this serious issue. A literature review was conducted to provide a comprehensive understanding of the factors influencing perceived employability among university students, focusing on research findings published since 2021. The present study indicates that numerous factors, including individual, behavioural, and environmental variables, significantly influence perceived employability among university students. Besides, previous research has diverged on specific factors such as demographics, partial components of personality traits, career engagement, political skills, and labour market situation, which need to be further investigated in the future. Furthermore, this study underscores the crucial significance of perceived employability among university students in a challenging job market. It validates the relevance of Career Construction Theory in interpreting perceived employability among university students and improves researchers’ understanding of how perceived employability has evolved before and after the pandemic. Most importantly, this study develops an integrated model of the factors influencing the perceived employability among university students, which can serve as a guide for future researchers to study university students’ employment issues and navigate the career practices of stakeholders such as the Ministry of Education, universities, university students, employers, and career practitioners.